Caring or Not Caring for Coworkers? An Empirical Exploration of the Dilemma of Care Allocation in the Workplace. Issue 4 (6th October 2020) - Antoni, Anne; Reinecke, Juliane; Fotaki, Marianna
ABSTRACT: Organization and management researchers praise the value of care in the workplace. However, they overlook the conflict between caring for work and for coworkers, which resonates with the dilemma of care allocation highlighted by ethicists of care. Through an in-depth qualitative study of two organizations, we examine how this dilemma is confronted in everyday organizational life. We draw on the concept of boundary work to explain how employees negotiate the boundary of their caring responsibilities in ways that grants or denies care to coworkers. We argue that the possibility of an ethics of care for coworkers requires boundary work that suspends the separation of personal and professional selves and constitutes the worker as a whole person. We contribute to research on care in organizations by showing how care for coworkers may be enabled or undermined by maintaining or suppressing the care allocation dilemma.